E-Service Quality, Online Customer Reviews, and Purchase Intention as the Moderating Role of Purchase Decision - Prabowo, Febryanto Agung; Utama, Rizky; Kartono, Rano (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The existence of technology has caused a change in people’s spending patterns, where initially, shopping was carried out in person, but now it can be done online. To increase the number of buyers, increasing the e-service quality for online sellers is necessary. This research will examine the influence of e-service quality, online customer reviews, and purchase intention as the moderating role of purchase decisions. This research will be carried out using a quantitative approach. The data analysis method used is the Structural Equation Model (SEM) analysis method with SmartPLS3 software. This research then finds that e-service quality and online customer reviews significantly affect purchase intention. Then purchase intention has a significant effect on the purchase decision. Lastly, e-service quality and online customer reviews affect purchase intention, which affects purchase decisions.